Perancangan Kursi Sekolah untuk Anak Autis yang Ergonomis dengan Pendekatan Metode Rasional - Sopyana, Eka; Jazuli, Jazuli (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2025)
This study designs ergonomic school chairs for children with autism, addressing their unique physical and sensory needs often neglected in schools. Conducted at SLB Yayasan Autisma Semarang, the research involved teachers and parents to identify user requirements, supported by students’ anthropometric data. The rational method guided the design, using the 5th, 50th, and 95th percentiles to ensure fit. The chair emphasizes comfort, safety, and sensory-friendly features through soft, heat-resistant materials, a safety belt, rounded edges, and a stable structure. Calm colors-gray, light blue, and pastel green-were chosen to reduce sensory overload. This inclusive design supports proper posture and comfort during learning.